Pengaruh Lokasi, Variasi Produk, Kualitas Pelayanan dan Suasana Toko Terhadap Keputusan Pembelian dimarwah Kiby Pare - Jihan Amelia; Baju Pramutoko; Trisnia Widuri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In this research, the influence of location, product variety, service quality and shop atmosphere on purchasing decisions at Marwah Kiby Pare can be explained. In this research, quantitative methods and analytical techniques used in this research are used, namely validity test, reliability test, correlation test, multiple linear test, t test (partial test), f test (simultaneous test), and coefficient of determination test. The sampling technique used in this research was incidental sampling and the sample used in this research was 99 respondents. In this research it can be concluded that location, product variety, service quality and store atmosphere have a positive and significant influence on purchasing decisions. And location, product variety, service quality and store atmosphere have a simultaneous and significant influence on purchasing decisions